The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.bpo.0000150814.56790.f9
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Foot Abduction Orthosis Following Ponseti Casts

Abstract: The purpose of this study was to evaluate the need for the use of a foot abduction orthosis (FAO) in the treatment of idiopathic clubfeet using the Ponseti technique. Forty-four idiopathic clubfeet were treated with casting using the Ponseti method followed by FAO application. Compliance was defined as full-time FAO use for 3 months and part-time use subsequently. Noncompliance was failure to fulfill the criteria during the first 9 months after casting. Feet were rated according to the Dimeglio and Pirani scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 7 publications
3
80
0
13
Order By: Relevance
“…Bor et al [2] observed that deviations from the Ponseti bracing recommendations were associated with a near twofold increase in additional operations. Excessive weight gain [4], parental educational level [8,12], a positive family history [8,12], and bracing noncompliance [8,9,11,21,28,31] have been identified as patient-related predictors of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Bor et al [2] observed that deviations from the Ponseti bracing recommendations were associated with a near twofold increase in additional operations. Excessive weight gain [4], parental educational level [8,12], a positive family history [8,12], and bracing noncompliance [8,9,11,21,28,31] have been identified as patient-related predictors of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Abduction splinting is an essential component of the Ponseti method, and relapse rates of up to 70% may be expected when the abduction splint is not worn [6,10,11,27]. Reasons for a lack of adherence to the splinting program may include noncompliance (patient or family chooses not to wear the splint) and brace intolerance (discomfort from skin irritation or other cause).…”
Section: Discussionmentioning
confidence: 99%
“…The economic and social consequences of time away from home must be recognized in a society where subsistence agriculture is the principle means of support. Realistically, this will involve the training of health professionals other than orthopaedic surgeons, and our experience suggests paraprofessionals may effectively administer the casting as shown in the United Kingdom (physiotherapists) [25] and Malawi (orthopaedic clinical officers) [27]. Such nonconventional models must be explored if clubfoot care is to be delivered at the population level in low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 displays the ranked difficulties with each component of the Ponseti method as indicated by 24/27 An overall response rate of 63% was achieved Of the 27 responses received, 24 (89%) indicated that the results achieved using the Ponseti method to correct clubfoot were either excellent [8] or moderate [9]. The respondents commented on the barriers to treatment, such as distance [5], poor follow-up [5], poor parent compliance, especially with the FAB [10], no FAB available [1], and older children [3].…”
Section: Survey Resultsmentioning
confidence: 99%